2017
DOI: 10.1111/birt.12282
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of defining and treating anemia and iron deficiency in pregnancy: A study of New Zealand midwives' management of iron status in pregnancy and the postpartum period

Abstract: There was a wide range in the midwives' practice. Maternal iron status was difficult to categorize, because of inconsistent testing. This study indicates the need for an evidence-based clinical guideline for New Zealand midwives and maternity care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In particular, the conflicting biological rationales, stated earlier, have made the clinical practice challenging and evidence-based recommendations are not readily available. [ 23 24 25 ] In summary, our findings may have three important implications for weight management and the use of iron supplements. First, our findings clearly emphasize, on top of other studies investigating adverse effects of excessive weight gain, that fast weight gain during pregnancy is undesirable.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, the conflicting biological rationales, stated earlier, have made the clinical practice challenging and evidence-based recommendations are not readily available. [ 23 24 25 ] In summary, our findings may have three important implications for weight management and the use of iron supplements. First, our findings clearly emphasize, on top of other studies investigating adverse effects of excessive weight gain, that fast weight gain during pregnancy is undesirable.…”
Section: Discussionmentioning
confidence: 90%
“…Although anaemia is associated with increased risk for significant morbidity and mortality 23,24 , there are no clear recommendations for postpartum anaemia testing 25 . Risk factors for postpartum anaemia were shown to be anaemia during the third trimester of pregnancy, postpartum haemorrhage, younger maternal age, and inadequate iron supplementation during the postpartum period 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…No studies reporting the frequency of iron deficiency and iron deficiency anemia in pregnant women in African countries were found. Research performed in Oceania showed no consensus regarding maternal anemia indicators [37][38][39]. Betwen 1999 and 2005, the occurrence of maternal anemia in southern Australia was 7.1% [37].…”
Section: Prevalence Of Maternal and Iron Deficiency Anemiamentioning
confidence: 99%
“…Betwen 1999 and 2005, the occurrence of maternal anemia in southern Australia was 7.1% [37]. In New Zealand, 2013 data indicate a frequency of maternal anemia of 54.5%; however, only 6.3% and 5.8% of the pregnant women had iron deficiency and iron deficiency anemia, respectively [39]. Another relevant indicator for this hematological disorder concerns the severity of maternal anemia [1].…”
Section: Prevalence Of Maternal and Iron Deficiency Anemiamentioning
confidence: 99%